A Clinical Investigation to Determine the Safety and Efficacy of a Novel, Patented Prunus Domestica Extract in Benign Prostatic Hyperplasia (BPH) - Sankhwar, S.N.; Verma, Narsingh; Patel, Naresh; Kumar, Pawan; Goel, Apurva; Rungta, Mehul (Functional foods in health and disease, 2025)
Background: The non-cancerous enlargement of the prostate gland frequently seen in males ofage over 50 years is known as Benign Prostate Hyperplasia (BPH). The major symptoms andailments of the disease involve difficulty in urination with dripping of urine, incompleteemptying of the urinary bladder and backflow of urine in extreme cases which may result inkidney infection. The conventional drugs based on alpha-adrenergic receptor antagonists or theType 2 5-alpha reductase inhibitors both of which have been found to be associated with seriousside effects. Phototherapeutics, especially phytosterols from the plum family, Prunus domesticaand Prunus africana have shown promising results in treatment of BPH especially throughreduction of prolactin levels and arresting accumulation of cholesterol in Prostate.Objectives: The present research was undertaken to carry out a robust clinical trial on the effectof Prosman TM , a novel patented and standardized extract of Prunus domestica in patientssuffering from BPH belonging in the age group of 40-65 years.Material and Methods: An open labeled single armed study in 140 male patients of BPH withinthe age group of 40-65 years. Prosman TM in dosage of 100 mg was administered twice a day for12 weeks with follow-ups at the end of 4, 8 and 12 weeks. Subsequently the efficacy of theproduct was assessed by biochemical tests including blood test for Prostate Specific antigen (PSA), Ultrasound and urinary flow test. Safety was ascertained through analysis of variousblood parameters including hemoglobin, total leukocyte count, differential leucocyte count,SGOT, SGPT and ALT levels as well as monitoring of urea and creatinine levels.Results: Prunus Domestica extract (Prosman TM ) was effective in alleviating BPH in patients asconfirmed by reduction in IPSS score, prostate volume and serum PSA levels. No significantadverse change was noted in the hematological parameters.Conclusion: Prunus Domestica extract (Prosman TM ) can therefore be explored as a safe andeffective phototherapeutics for development of novel treatment procedures of BPH.